Perceptions of Residents and Police Officers on the Implementation of Community Policing Program in Nyaribari Chache Sub-County, Kenya - Martin Munene Gichobi; Dr. Elijah Onyango Standslause Odhiambo (IJRDO - Journal of Social Science and Humanities Research, 2020)
This study sought to assess the effectiveness of implementation of community policing program as a crime prevention strategy in Nyaribari Chache Sub-County, Kenya. Effective implementation of community policing program in Kenya and Nyaribari Chache Sub-County specifically has not been entirely successful due to the poor relation between the police and the community who are key stake holder in the implementation of community policing program. In Kenya police reforms is a critical issue not only for community safety and economic development, but because there is intense popular demand for reduced crime and better police performance. The programme aims to improve relation between the police and the communities and to enable them to work together to find solutions to community safety concerns. However, there continue to be major obstacles to police reforms in Kenya, crime rates area still high, there is widespread corruption and policing approaches and actors are often politicised. These challenges alongside the uneven pace of reforms have limited progress in extending CBP. The study focus was on the effectiveness of the implementation of Community Policing program as a crime prevention strategy. The specific objective of the study was to examine the perceptions of residents and police officers on the implementation of community policing program in Nyaribari Chache Sub-County. This study was inclined on social theories of criminology that lay the basis of the study. The research methodology and methods covered the research design which includes descriptive and explorative research, variables, and area of the study, target population, sampling procedure and sample size, research instruments such as the use of questionnaires, interviews and focused group studies. It also covered on the pilot study, reliability and validity of the data, data collection procedure, data processing and analysis as well as data management and ethical considerations.This study aimed at finding out how community policing program implementation has impacted on crime reduction. The findings of this study are very crucial in formulation of policies and laying out of strategies that will greatly help in effective implementation of community policing which is very crucial in curbing of crimes in the society hence restoring order.